PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 002 JUMRAH KECAMATAN RIMBA MELINTANG - Surijah Surijah; Hendri Marhadi; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Absrtact : This Research background is lowering of result of learning mathematics of student of class of IV SD Negeri 002 Jumrah Kecamatan Rimba Melintang. With the mean of result of learning student 57,60. From 25 student people only 7 people ( 28%), tired of KKM, while which do not reach the KKM as much 18 people ( 72%), while standard KKM specified by a school is 70. This research is done/conducted by as much 2 cycle by 6 is meeting times;rill, consisted of by 4 times items presentation and 2 times daily restating. After execution of study and data collecting. Data processed and analysed. Result of data analysis show at daily restating ( UH I) happened by the make-up of mean of result of learning from elementary score 57,60 becoming 67,20 mounting 9,6 poin ( 14,29%) and from daily restating of I to daily restating of II ( UH II) happened by the improvement of equal to 18 ( 21,13%) so that become 85,20. Becoming by klasikal from elementary score to daily restating of II ( UH II) happened by the improvement 27,6 poin ( 32,39%). From other sideing that is also happened by the complete improvement of klasikal from score 28% at restating of cycle I mount as much 24% so that percentage become 52% and at restating of cycle II mount as much 36% so that percentage become 88%. Is and also happened by the make-up of activity learn and student in each meeting. For the activity of learn at first meeting of cycle I of equal to 66,70% mounting at second meeting of cycle II become 79,20% ( 12,5%), from second meeting of cycle II to first meeting of cycle II become 87,50% ( 8,3%), and from first meeting to second meeting of cycle II become 95,80% ( 8,3%). For the activity of student of at first meeting equal to 62,50% mounting to second meeting become 70,80% ( 8,3%), from second meeting of cycle I to first meeting of cycle II become 83,3% ( 12,50%), and from first meeting of cycle II to second meeting of cycle II become 91,70% ( 8,40%). Becoming inferential that applying model the study STAD can improve the result learn the mathematics of student of class of IV SD Negeri 002 Jumrah Kecamatan Rimba Melintang.Keyword : Model the Study of Co-Operative of type STAD, result of learning mathematics, PTK